Delayed extubation and hypertrophic pyloric stenosis: what are the predictive factors? - Youssef, Sabrine Ben; Laribi, Syrine; Chakroun, Sawsen; Mansour, Maha Ben; Fredj, Mariem Ben; Toumi, Afef; Salah, Radhouen Ben; Ksia, Amine; Mekki, Mongi; Belghith, Mohsen; Belhassen, Samia; Sahnoun, Lassaad (Frontiers in Pediatrics, 2025)
IntroductionProlonged time to extubation after general anesthesia has been defined as a delay of more than 15 min from the end of surgery to tracheal extubation. This incident is frequently seen in infants operated on for hypertrophic pyloric stenosis (HPS), which can lead to inefficient use of operating rooms and delayed care for other patients.AimTo evaluate the frequency of “delayed extubations” in infants who have received an extramucosal pyloromyotomy under general anesthesia and to identify the predictive factors of this incident.MethodsWe report a retrospective and comparative study of patients operated for HPS at the pediatric surgery department of Monastir, between January 2020 and December 2023.ResultsThirty-four cases were collected. Delayed extubation occurred in 19 cases with very prolonged extubation (>60 min) in 3 cases. The mean age at diagnosis was 38.07 days for group 1 and 34.42 days for group 2. The average of operating time was 56 min for both groups. On the χ2 test, the difference between the groups was significant for metabolic alkalosis. However, the results were not significant for the other criteria (prematurity, hypotrophy, dehydration, hyponatremia, hypochloremia, hypokalemia, functional renal failure, pre-operative resuscitation time).ConclusionsThese data suggest that metabolic alkalosis is predictive of delayed extubation in infants operated on for HPS under general anesthesia. The use of spinal anesthesia may be an alternative to general anesthesia but it remains a controversial issue, as there are few comparative data.